Work on your guanxi. - Guishan, Yang; Richardson, Paul (Bookseller, 2003)
Assess the Chinese market for books analyzing opportunities offered by the Beijing International Book Fair 2003. Size of the book market; Information on channels of distribution of books; Attempt made by Western publishers to enter into partnership with Chinese firms. INSETS: China as a book market;Chinese economic growth;Opportunities at the book fair and beyond.